COMPARATIVE STUDY OF DIGITAL THERMOMETRY AND INFRARED THERMOGRAPHY FOR TEMPERATURE MEASUREMENT IN A PRIVATE DENTAL SERVICE – PILOT STUDY - Silva dos Santos, Nicolas; Accioly Valentin dos Santos, Roberta; Wolf Bueno Picão, Pedro; Carvalho, Fernanda; Souza Lima, Sarah; Peixoto Medrado, Alena (Revista da Faculdade de Odontologia da Universidade Federal da Bahia, 2023)
Purpose: The purpose of this study was to analyze the temperatures measured through conventional digital thermometry and infrared thermography comparatively, in a group of patients from a private dental health service. Materials and methods: A convenience retrospective sample of 25 female patients, were submitted to temperature recordings using thermograms of the brain thermal tunnel (BTT) and frontal region, and digital thermometry in the frontal region. The data obtained from the two anatomical sites evaluated were statistically analyzed to create a temperature dispersion graph. Results: It was observed that the mean temperature measured with the digital thermometry was 36.3ºC with a standard deviation of ±0.60, and was the one that presented the highest value in relation to Infrared Thermography, as well as less variation of average individual temperatures(p<0.05). Final considerations: Digital thermometry showed low specificity, while Infrared Thermography proved to be a tool with greater sensitivity for measuring body temperature, especially in the BTT region.